The Use of Narrative Features to Reframe Egypt Military Coup News - Rina Fajrin (Universitas Pendidikan Indonesia (UPI), 2016)
This present research examined narrative features used to reframe Egypt military coup news. The data were in the form of two articles taken from Al-Arabiya as the source texts and two articles taken from Kompas as the target texts. This research employed qualitative approach and descriptive method as research design and textual analysis to collect the data. To analyse the data, this research used narrative theory proposed by Baker (2010a). According to the results, this research showed that narrative features used are selective appropriation, temporality, and relationality. Selective appropriation is the most frequently used in this study which means that the texts were purposively selected to represent the target text news agency. By using temporality, the texts underwent an adjustment of time with the time in the target texts. In addition, temporality also made the texts reveal a distance between the readers and the place where the incident happened. Furthermore, by applying relationality, the texts underwent an adjustment with the understanding which existed in the target texts. Based on the findings, this study concludes that Al-Arabiya tended to support Ikhwanul Muslmin and Kompas tended to support Egypt military.Keywords: Narrative, Narrative Features, Reframing, and News